2018
DOI: 10.1371/journal.pone.0196723
|View full text |Cite
|
Sign up to set email alerts
|

MPT64 antigen detection test improves routine diagnosis of extrapulmonary tuberculosis in a low-resource setting: A study from the tertiary care hospital in Zanzibar

Abstract: BackgroundExtrapulmonary tuberculosis (EPTB) is a diagnostic challenge. An immunochemistry-based MPT64 antigen detection test (MPT64 test) has reported higher sensitivity in the diagnosis of EPTB compared with conventional methods. The objective of this study was to implement and evaluate the MPT64 test in routine diagnostics in a low-resource setting.MethodsPatients with presumptive EPTB were prospectively enrolled at Mnazi Mmoja Hospital, Zanzibar, and followed to the end of treatment. Specimens collected we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 25 publications
4
48
3
1
Order By: Relevance
“…Thus, the MPT64 test may strengthen the TB diagnosis in a pathology laboratory in the absence of culture confirmation. The MPT64 test performance was lower in the present study compared to previous studies [28][29][30]35]. Against a CRS, the overall sensitivity was 32% (95% CI 17-51) for the MPT64 test, compared to 67-100% in previous studies [28][29][30]35].…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Thus, the MPT64 test may strengthen the TB diagnosis in a pathology laboratory in the absence of culture confirmation. The MPT64 test performance was lower in the present study compared to previous studies [28][29][30]35]. Against a CRS, the overall sensitivity was 32% (95% CI 17-51) for the MPT64 test, compared to 67-100% in previous studies [28][29][30]35].…”
Section: Discussioncontrasting
confidence: 88%
“…All previous studies were conducted in high TB burden settings, in which a higher pre-test probability of TB combined with potentially more advanced stage of TB disease at the time of diagnosis, may lead to higher test sensitivity. Still, also when using culture as a reference standard, the overall MPT64 test sensitivity was lower (19, compared to previous studies (75-100%) [26,28,30,35,37]. This could partly be explained by different procedures for culture used across the studies.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Jørstad et al used immunohistochemistry to detect MPT64 antigen in 132 cases of extrapulmonary tuberculosis and non-tuberculosis specimens. MPT64 detection had the best performance in TB lymphadenitis patients and children with TB, suggesting that MPT64 detection could be used for routine diagnosis under low resource allocation to improve the diagnosis of extrapulmonary tuberculosis, especially for tuberculous lymphadenitis and children with TB [39] . Purohit et al studied 51 cases of pulmonary tuberculosis and 38 control specimens of non-pulmonary tuberculosis.The results suggested that anti-MPT64 immunostaining detection was a rapid and sensitive method for early specific diagnosis of Mycobacterium tuberculosis infection [40] .…”
Section: Detection Of Mtbc By Intestinal Tuberculosis Protein Combinementioning
confidence: 99%